2022
DOI: 10.35335/midwifery.v10i5.910
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Service Quality and Outpatient Satisfaction at the Langga Payung Health Center, South Labuhanbatu Regency in 2022

Abstract: Community satisfaction with health services is not only related to recovery from illness. Community satisfaction is related to the quality of service at the Puskesmas. Service quality is divided into five dimensions, namely physical evidence, reliability, responsiveness, assurance and empathy. This study aims to determine the relationship between service quality and outpatient satisfaction at the Langga Payung Health Center in South Labuhanbatu Regency in 2022. This research is a quantitative study with a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…The results of this study are in line with the research of Ayu Aulia Septiani (2015), it was found that there is a relationship between the dimension of responsiveness of outpatient health services and patient satisfaction at the Poncol Semarang Health Center with a p-value of 0.024. The results of the research by Djeinne Thresye Pangerapan (2018) showed that there was a relationship between responsiveness and patient satisfaction at the Internal Medicine…”
Section: Analysis Of the Relationship Of Responsiveness Dimensions To...supporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are in line with the research of Ayu Aulia Septiani (2015), it was found that there is a relationship between the dimension of responsiveness of outpatient health services and patient satisfaction at the Poncol Semarang Health Center with a p-value of 0.024. The results of the research by Djeinne Thresye Pangerapan (2018) showed that there was a relationship between responsiveness and patient satisfaction at the Internal Medicine…”
Section: Analysis Of the Relationship Of Responsiveness Dimensions To...supporting
confidence: 89%
“…The results of this study are the same as the research of Ayu Aulia Septiani (2015), it was found that there was a relationship between the dimensions of reliability of outpatient health services and patient satisfaction at the Poncol Semarang Health Center with a p-value of 0.017. The results of this study are also the same as the research of Maya Dewi Hanggraningrum (2017), there is a positive and significant relationship between the reliability variable and outpatient satisfaction at Dr. Soegiri Lamongan Hospital with a result of 5,888 and a p-value of 0.001.…”
supporting
confidence: 81%